Cancer knowledge and health-consciousness in childhood cancer survivors following transition into adult care—results from the ACCS project - Otth, Maria; Denzler, Sibylle; Diesch-Furlanetto, Tamara; Scheinemann, Katrin (Frontiers in Oncology, 2022)
Background Knowledge on chronic medical conditions in childhood cancer survivors (CCS) is constantly growing and underlines that long-term follow-up (LTFU) care is often mandatory, also in adulthood. However, many CCS discontinue follow-up care after transition to adult care. One reason might be that the current transition practices do not meet the needs of adolescent and young adult CCS. We therefore aim to evaluate different transition model for Swiss CCS by assessing their cancer knowledge, cancer worries, self-management skills and expectations for LTFU care following transition in two different hospital-based models. Methods Within the Aftercare of Childhood Cancer Survivors (ACCS) study we performed a questionnaire-based survey with a cross-sectional and longitudinal part. We included 5-year CCSs aged >16 years at recruitment who were transitioned to adult care in two hospitals between 2014 and 2021. Here we report the results of the cross-sectional part. We compared the survivors’ cancer knowledge with medical record data and assessed cancer worries (6 questions), self-management skills (15 questions) and expectations (12 questions) by validated scales. We used descriptive statistics, chi-squared and t-test to describe the results. Results We analysed 57 CCS (response rate 44%), 60% of those were female, had a median age of 9 years at diagnosis and 23 years at questionnaire. Most CCS recalled their diagnosis (95%) and exposure to treatment modalities (98%) correctly. CCS worried the most about potential late effects (47%) and issues having children in the future (44%). At least 75% of CCS agreed to 12 of the 15 self-management questions, indicating high self-management skills. The top three expectations included that physicians know the survivors’ cancer history, that visits start on time and that physicians can always be called in case of questions. Conclusion CCS receiving hospital-based LTFU care have a good cancer knowledge and high self-management skills. The identified worries and expectations will help to improve LTFU care of CCS who transition to adult care, to further inform and educate survivors and health care professionals about and might be relevant for other countries with a similar heath care system.